IGF-1R and mTOR Blockade: Novel Resistance Mechanisms and Synergistic Drug Combinations for Ewing Sarcoma. (30th August 2016) - Lamhamedi-Cherradi, Salah-Eddine; Menegaz, Brian A.; Ramamoorthy, Vandhana; Vishwamitra, Deeksha; Wang, Ying; Maywald, Rebecca L.; Buford, Adriana S.; Fokt, Izabela; Skora, Stanislaw; Wang, Jing; Naing, Aung; Lazar, Alexander J.; et al.
Abstract : Background: Therapies cotargeting insulin-like growth factor receptor 1 (IGF-1R) and mammalian target of rapamycin (mTOR) have demonstrated remarkable, albeit short-lived, clinical responses in a subset of Ewing sarcoma (ES) patients. However, the mechanisms of resistance and applicable strategies for overcoming drug resistance to the IGF-1R/mTOR blockade are still undefined. Methods: To elucidate predominant mechanism(s) of acquired drug resistance while identifying synergistic drug combinations that improve clinical efficacy, we generated more than 18 ES cell lines resistant to IGF-1R- or mTOR-targeted therapy. Two small-molecule inhibitors of IGF-1R were chosen, NVP-ADW-742 (IGF-1R-selective) and OSI-906 (a dual IGF-1R/insulin receptor alpha [IR-α] inhibitor). Reverse-phase protein lysate arrays (RPPAs) revealed proteomic changes linked to IGF-1R/mTOR resistance, and selected proteins were validated in cell-based assays, xenografts, and within human clinical samples. All statistical tests were two-sided. Results: Novel mechanisms of resistance (MOR) emerged after dalotuzumab-, NVP-ADW-742-, and OSI-906-based targeting of IGF-1R. MOR to dalotuzumab included upregulation of IRS1, PI3K, and STAT3, as well as p38 MAPK, which was also induced by OSI-906. pEIF4E(Ser209), a key regulator of Cap-dependent translation, was induced in ridaforolimus-resistant ES cell lines. Unique drug combinations targeting IGF-1R and PI3K-alpha or Mnk and mTOR were synergistic in vivo and vitro ( P < .001) as assessed respectively by Mantel-Cox and isobologram testing. Conclusions: We discovered new druggable targets expressed by chemoresistant ES cells, xenografts, and relapsed human tumors. Joint suppression of these newfound targets, in concert with IGF-1R or mTOR blockade, should improve clinical outcomes.